ANALISIS DAMPAK EKSTERNALITAS ADANYA PENGANGKUTAN TANAH DARI DAERAH PERTAMBANGAN TERHADAP INFRASTUKTUR JALAN (STUDI KASUS DI DESAKALIPANCUR, BOJONG) (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2022)
Roads are the main needs of the community as a liaison in carrying out activities, especially economic activities. The condition of the road surface must be maintained properly to provide good service to road users. However, road damage is unavoidable for various reasons. Road users' non- compliance with road administration regulations that have been set by the government, such as violations of load restrictions can cause road damage. From the results of research related to the impact of land mining on road infrastructure in the village of Kalipancur, Bojong as well as data from BPS Pekalongan Regency, it is concluded that the actors of the damage to road infrastructure are the presence of overloaded vehicles and the increase in rainfall levels in the village.